PENENTUAN WAKTU SALAT ZUHUR DENGAN BATAS AWAL ZAWÂL AL-SYAMS - Badrun Taman; Fafa Redy (Faculty of Sharia (Islamic Law) at Fatmawati Sukarno State Islamic University Bengkulu, 2019)
There are two different consepts of zawâl al-syams. First consept shows that zawâl al-syams is sun position when it’s east disk get through meridian. Second consept talk that the zawâl al-syams is sun position which it’s center point accros meridian. This different implicate that doing zuhur prayer when sun is in istiwa’ position is legitimated according to second consept, and isn’t legitimated in the view of first consept, because it doesn’t enter initial limit of zawâl al-syams yet. This description bring up two problems, there are: how is the zawâl al-syams consept according to Islamic jurisprudence of prayer time, and how is the initial limit of zawâl al-syams in the view of Islamic prayer time jurisprudence. This is qualitative-library research with descriptif-analitical-comparative method and normative-astronomic approach. The research conclusions are zawâl al-syams in Islamic jurisprudence perspective is zawâl zhahiri (observable zawâl) with zhuhur fai’ al-zawâl criteria means appearance of zawâl shadow. So that, Zawâl zhahiri is slipping of the sun from meridian signed bay appearance of shadow increase ini length moving to the east. Initial limit of zawâl is started from the first motion of sun